Planejamento em reabilitação oral: restabelecimento da relação intermaxilar por meio de prótese provisória overlay - Goiato, Marcelo Coelho [UNESP]; Pellizzer, Eduardo Piza; Santos, Daniela Micheline dos; Moreno, Amália (My University, 2012)
The present article describes the treatment planning and fabrication of overlay denture to restore the jaw relationship in a partial edentulous patient with bruxism. A male patient, 51 years old, was referred to the oral rehabilitation clinic complaining about the chewing and aesthetic. The occlusal surface of the superior teeth presented severe wear. The fabrication of an interim overlay denture to restore the jaw relationship was planned. The overlay had metallic projections and covered the occlusal surface of superior teeth. After overlay insertion both function and aesthetic of the patient were recovered. It was concluded that the use of overlay improved the physiological normal position of the jaw and could provide a favorable prognosis for a definitive oral rehabilitation with implant-supported fixed denture.

Este trabalho descreve o planejamento e confecção de prótese overlay para restabelecer a relação intermaxilar em paciente parcialmente dentado com bruxismo. Paciente do sexo masculino, com 51 anos de idade, compareceu para reabilitação oral queixando-se da dificuldade de mastigação e estética. O paciente apresentava alto grau de desgaste oclusal nos dentes remanescentes da arcada superior. O planejamento foi a confecção de prótese overlay provisória superior para restabelecimento da relação intermaxilar. Após a instalação da prótese overlay com projeções metálicas e recobrimento oclusal em todos os dentes, as alterações na função e estética apresentaram-se clinicamente satisfatórias para o paciente. Pode-se verificar com o uso da prótese melhora na posição fisiológica normal para posterior reabilitação oral definitiva por meio de próteses fixas sobre implante.
Oral rehabilitation planning: restoring the jaw relationship by using na interim overlay denture
Keywords: Removable denture; Bruxism; Vertical dimension; Prótese removível; Bruxismo; Dimensão vertical